Faktor-faktor yang Memengaruhi Tax Avoidance : Studi Empiris Pada Perusahaan BUMN di BEI - Hafia'annida Firdaus Az-zahra; Rina Trisnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Tax avoidance can be interpreted as a strategy to reduce tax liabilities and is allowed in the eyes of the law but has a significant impact on reducing government tax revenues. This study aims to prove whether tax avoidance is influenced by transfer pricing, political connections, accounting conservatism, fiscal loss compensation and sales growth. The object of research includes 150 state-owned companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. Tax avoidance is measured by Effective Tax Rate (ETR). A sample of 91 companies was taken using purposive sampling method. The results showed that transfer pricing variables, political connections, accounting conservatism and sales growth have no influence on tax avoidance, while fiscal loss compensation variables have an influence on tax avoidance